Flood Modeling Using HEC-RAS Based on Extreme Rainfall Data - Glory San-Deo (Civil Engineering Science and Technology, 2026)
Flooding remains one of the most significant hydrological hazards in many river basins, particularly as extreme rainfall events intensify. This study employs a quantitative research design based on hydrological and hydraulic modeling to analyze flood behavior under extreme rainfall scenarios. The research integrates extreme rainfall frequency analysis, rainfall–runoff transformation, and hydraulic simulation using HEC-RAS, developed by the U.S. Army Corps of Engineers. Design rainfall for multiple return periods was analyzed and converted to peak discharge, which was subsequently used as input to a hydraulic simulation to generate water surface elevation profiles, flow velocity distributions, and flood inundation maps. The results indicate a progressive increase in peak discharge and inundation extent with higher return periods, with a more pronounced hydraulic response under extreme recurrence intervals. Flooding at lower return periods remains confined within the river channel, whereas at higher return periods, flows exceed channel capacity and significantly expand inundation areas. These findings highlight the importance of integrated quantitative modeling in supporting flood risk assessment, river capacity planning, and resilient spatial development strategies. The proposed modeling framework provides a comprehensive basis for linking extreme rainfall characteristics to spatial flood hazard mapping in water resources management.